2019
DOI: 10.1002/jrs.5734
|View full text |Cite
|
Sign up to set email alerts
|

H2O2induced hydrogen bond water networks enhanced on stimulated Raman scattering

Abstract: Forward stimulated Raman scattering in pure water and H2O2–H2O mixture solutions are investigated under different pump laser energies. Three characteristic peaks are observed in mixture solutions due to the enhancement of hydrogen bonds (H‐bonds) structure of water molecules by H2O2. Simultaneously, stimulated Raman scattering lines indicate that high‐pressure ice‐phase is formed in mixture solutions, which is attributed to the reduction of the laser breakdown threshold of liquid water by H2O2, resulting in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The application of this new approach to SRS microscopy allows greater insight into deep‐lying structures in a noninvasive way. Wang et al [ 111 ] demonstrated the coexistence of ice‐like and quartz‐like structure in localized liquid water by stimulated Raman scattering. The two structures show different pressure‐dependent behaviors based on the SRS results; meanwhile, the distribution of two structures is different in the bulk and on the surface of water.…”
Section: Nonlinear Coherent and Time‐resolved Raman Spectroscopymentioning
confidence: 99%
“…The application of this new approach to SRS microscopy allows greater insight into deep‐lying structures in a noninvasive way. Wang et al [ 111 ] demonstrated the coexistence of ice‐like and quartz‐like structure in localized liquid water by stimulated Raman scattering. The two structures show different pressure‐dependent behaviors based on the SRS results; meanwhile, the distribution of two structures is different in the bulk and on the surface of water.…”
Section: Nonlinear Coherent and Time‐resolved Raman Spectroscopymentioning
confidence: 99%